(untitled) (Scientific journal of the Fergana State University, 2025)
Jadidism, which emerged in the late 19th century, played a key role in transforming Muslim societies within the Russian Empire. This movement was not merely a cultural reform but an attempt to rethink traditional norms in the context of a rapidly changing world. Key themes in the activities of the Jadids included the struggle against polygamy, ideas of gender equality, and secularism. This article examines these aspects, analyzes the prerequisites for their emergence, and evaluates their impact on social life.